Quantitative Evaluation of a Cross-Sectional Area of the Fetal Straight Sinus by Magnetic Resonance Imaging and Its Clinical Value - Fu, Shi-Jia; Xu, Jing-Bo; Liu, Xin; Cao, Yi-Min; Yi, Ze-Xi; Zhou, Li-Xia (Frontiers in Neurology, 2022)
Objective: The intracranial venous system plays an important role in ensuring blood circulation and a stable blood supply to the fetal brain. In the present study, a cross-sectional area of the fetal straight sinus was quantitatively evaluated by fetal magnetic resonance imaging (MRI) to explore the method’s clinical value. Methods: The clinical and MRI data of 126 normal fetuses in mid-to-late stage pregnancies were retrospectively analyzed. The "dominant" sequence of the fetal straight sinus was selected, and the cross-sectional area of the lumen was measured at each gestational age to obtain the normal range at different ages and to analyze the developmental pattern and characteristics of the fetal straight sinus. Results: There were statistically significant differences in the cross-sectional area of the fetal straight sinus among different gestational ages (P < 0.05). The cross-sectional area of the fetal straight sinus was positively correlated with gestational age (coefficient of determination = 0.6892, P < 0.05). That is, the cross-sectional area of the fetal straight sinus grew with increasing gestational age, and the regression equation was y = 0.27 x –2.14 (P < 0.05). Additionally, there were 5 fetuses with cerebral venous abnormalities, including 4 with heart failure and 1 with venous sinus thrombosis. Conclusion: Quantitative measurement of a cross-sectional area of the fetal straight sinus by MRI enhanced understanding of the anatomical features and developmental pattern of fetal cerebral veins and provided a reference for the clinical diagnosis of related diseases and investigation concerning pathogenesis.